Architectonic peculiarities of publications different in social and functional purpose with stereo illustrations - Nazarkevych, Y. (Theory and practice of design, 2016)
Book architectonics is discussed in terms of the synthesis of the content of artistic image creation and design. Specific artistic image, its special aesthetic and atmospheric mobilizing role of stereo and vario images are described. Architectonic peculiarities of books with anaglyph and lenticular illustrations are analyzed (textbooks, popular scientific publications, children’s books, encyclopedias). It is shown that stereoscopy provides wide possibilities for the designer in developing the book architectonics, while transforming stereo illustrations in pictorial material of the book.